Exploring The Link Between Counterproductive Work Behavior and Job Performance : Narrative Review - Purwatiningsih, Purwatiningsih; Alan Budi Kusuma; Frida Aprillia; Dhuha Safria (Cahaya Abadi Publisher, 2025)
Counterproductive Work Behavior (CWB) has been widely recognized as a major challenge affecting job performance in organizations. This study provides a narrative review of existing literature to analyze the impact of CWB on different dimensions of job performance, including task performance, contextual performance, and adaptive performance. By synthesizing findings from various studies, this review identifies key factors influencing the relationship between CWB and job performance, such as organizational culture, leadership styles, and workplace justice. Additionally, the study highlights gaps in the literature and suggests future research directions to better understand and mitigate the negative effects of CWB.